2015
DOI: 10.1007/s10971-015-3882-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property tuning in hydrothermally stable sol–gel-processed hybrid organosilica molecular sieving membranes

Abstract: Supported microporous organosilica membranes made from bridged silsesquioxane precursors by an acid-catalyzed sol-gel process have demonstrated a remarkable hydrothermal stability in pervaporation and gas separation processes, making them the first generation of ceramic molecular sieving membranes with sufficient performance under industrially relevant conditions. The commercial availability of various a,x-bis(trialkoxysilyl)alkane and 1,4-bis(trialkoxysilyl)benzene precursors facilitates the tailoring of memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…It is possible that during the hydrothermal treatment, as used in our work some traces of oxygen were still present, which would lower the onset temperature of decomposition. Similar changes in onset temperature were reported in a review paper of Ten Elshof et al [15], he observed that the in literature reported upper temperature limits varies significantly for the bridging ethylene groups under inert atmosphere from 250 to 500°C.…”
Section: Hydrothermal Stability Tests Under Simulated Wgs Conditionssupporting
confidence: 86%
See 4 more Smart Citations
“…It is possible that during the hydrothermal treatment, as used in our work some traces of oxygen were still present, which would lower the onset temperature of decomposition. Similar changes in onset temperature were reported in a review paper of Ten Elshof et al [15], he observed that the in literature reported upper temperature limits varies significantly for the bridging ethylene groups under inert atmosphere from 250 to 500°C.…”
Section: Hydrothermal Stability Tests Under Simulated Wgs Conditionssupporting
confidence: 86%
“…In literature several features are mentioned [15] for the increased hydrothermal stability. Very often the hydrothermal stability is ascribed to an increase of the hydrophobicity or the non-polarity, introduced by the organic groups, resulting in a reduction of the diffusion of water into the membrane.…”
Section: Fast Hydrothermal Stability Testmentioning
confidence: 99%
See 3 more Smart Citations